Plasma but not serum brain-derived neurotrophic factor concentration is decreased by oral glucose tolerance test-induced hyperglycemia in children - Araki, Shunsuke; Yamamoto, Yukiyo; Saito, Reiko; Kawakita, Aoi; Eguchi, Mami; Goto, Motohide; Kubo, Kazuyasu; Kawagoe, Rinko; Kawada, Yasusada; Kusuhara, Koichi (Journal of Pediatric Endocrinology & Metabolism, 2017)
Little is known regarding the relationships among circulating brain-derived neurotrophic factor (BDNF) levels and glucose or insulin in children and adolescents. The objective of this study was to investigate whether circulating BDNF levels would change during the oral glucose tolerance test (OGTT). We performed the OGTT and measured the serial changes in BDNF levels in both plasma and serum. There were 22 subjects in the normal type (N) group and 20 in the borderline/diabetic type (B/D) group, defined by the results of the OGTT. Serum levels of BDNF were almost five times higher and plasma levels gradually decreased during the OGTT, whereas serum levels showed no significant change. The reduction of plasma BDNF level changes from baseline to 120 min were significantly different between the N and B/D groups (36.3% vs. 20.8%, p=0.023). Our results showed that plasma levels of BDNF are more sensitive to acute changes in glucose or insulin levels than serum.